Pengaruh Digital Marketing dan User Experience Terhadap Keputusan Penggunaan Gojek Melalui Brand Image - Iskandar, Muflih; Saidani, Basrah; Aditya, Shandy (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2023)
The purpose of this study was to determine 1) the effect of digital marketing on usage decisions, 2) the influence of user experience on usage decisions, 3) the infIuence of digitaI marketing on brand image, 4) the infIuence of user experience on brand image, 5) the influence of brand image on usage decisions. , 6) infIuence of digitaI marketing on usage decisions through brand image, 7) infIuence of user experience on usage decisions through brand image. The study was conducted on 200 Gojek users in Jakarta who have used Gojek for at Ieast one year, using the SEM method and AMOS tooIs. The resuIts show that 1) digitaI marketing has a significant and positive effect on usage decisions, 2) user experience has a significant and positive effect on usage decisions, 3) digitaI marketing has a significant and positive effect on brand image, 4) user experience significantly and positive effect on brand image, 5) brand image has a significant and positive effect on usage decisions, 6) digitaI marketing has a significant and positive effect on usage decisions through brand image, 7) user experience has a significant and positive effect on usage decisions through brand image